Tasawuf Falsafi Dan Implikasinya Dalam Pendidikan Islam - Muhammad Anas Ma`arif (Vicratina : Jurnal Ilmiah Keagamaan, 2018)
The importance of knowing in depth philosophy of Sufi in order to avoid misunderstanding in learning or even practicing the teachings. The philosophical philosophy in view by some Sunni musicologists as a bad teaching for the layman. Some cases like Al-Hallaj were the victims of the government at the time. Or in the context of Indonesia such as the teachings of Siti Jenar with